Anxiety and Depressive Symptoms in Patients with COPD: Modifiable Explanatory Factors. (April 2023) - Bugajski, Andrew; Morgan, Hailey; Wills, Walter; Jacklin, Kellcee; Alleyne, Shirley; Kolta, Bishoy; Lengerich, Alexander; Rechenberg, Kaitlyn
Anxiety and depressive symptoms affect up to 80% of people with chronic obstructive pulmonary disease (COPD). To reduce this symptom burden, clinicians should target modifiable explanatory factors while accounting for nonmodifiable explanatory factors of these symptoms. The purpose of this secondary data analysis was to examine which modifiable factors explain anxiety and depressive symptoms in COPD. This secondary data analysis of 1, 760 COPD patients used multiple regression to explain anxiety and depressive symptoms from sets of modifiable patient characteristics and demographic controls. Clinically significant symptoms of anxiety or depression presented in 29.6% ( n = 526) of participants, and 20.6% ( n = 363) had both. Significant modifiable explanatory factors of both disorder symptoms were perceived functional status, functional capacity, psychosocial impact, symptom self-management, and significant symptoms for the other. Somatic symptom burden and dyspnea explained anxiety and depressive symptoms, respectively. Addressing these modifiable factors may reduce anxiety and depressive symptoms in patients with COPD.